2000
DOI: 10.1183/09031936.00.16510010
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae and the lung

Abstract: Chlamydia pneumoniae and the lung. M.R. Hammerschlag. #ERS Journals Ltd 2000. ABSTRACT: Chlamydia pneumoniae is a frequently occurring respiratory pathogen affecting all age groups. It may cause 5±20% of community-acquired pneumonias in adults and children. The organism has also been implicated as an infectious trigger for asthma. Furthermore, new studies suggest that it may play a role in the pathogenesis of several chronic diseases including atherosclerosis.However, despite the growing significance of C. pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 55 publications
2
63
0
6
Order By: Relevance
“…Most respiratory infections caused by C. pneumoniae are mild or asymptomatic. Many studies have suggested a possible association of C. pneumoniae infection and acute exacerbations of asthma and chronic obstructive pulmonary disease (14,15,19,26,30). Seroepidemiological studies showing antibody prevalence rates in a range of 50 to 70% suggest that C. pneumoniae is widely distributed and that nearly everybody is infected with the agent at some time (15,19,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most respiratory infections caused by C. pneumoniae are mild or asymptomatic. Many studies have suggested a possible association of C. pneumoniae infection and acute exacerbations of asthma and chronic obstructive pulmonary disease (14,15,19,26,30). Seroepidemiological studies showing antibody prevalence rates in a range of 50 to 70% suggest that C. pneumoniae is widely distributed and that nearly everybody is infected with the agent at some time (15,19,24).…”
Section: Discussionmentioning
confidence: 99%
“…Seroepidemiological studies showing antibody prevalence rates in a range of 50 to 70% suggest that C. pneumoniae is widely distributed and that nearly everybody is infected with the agent at some time (15,19,24). Several surveillances of community-acquired pneumonia (CAP) have demonstrated that C. pneumoniae is the second to fourth leading pathogen of CAP, and it is believed to be responsible for 6 to 22% of CAP cases, varying with the geographical location, the age group examined and the diagnostic methods used (15,19,23). Chronic C. pneumoniae infection is currently of considerable interest because of its link to atherosclerosis (6,19,31,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pharyngitis, sinusitis, and otitis), central and lower airways (e.g. bronchitis, brochiolitis), as well as lung tissue (pneumonia) [6,8,10,21,38]. The phenomenon of chronicity and persistence, however, is thought to be involved in the pathogenesis of chronic inflammatory airway diseases, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas most respiratory infections with C. pneumoniae are self-limited (4), bacterial colonization can lead to infectious exacerbations and development of COPD (5). Because detection rate of C. pneumonia varies significantly (6), the clinical relevance of C. pneumoniae is still controversial.…”
mentioning
confidence: 99%